Spontaneous re-eruption of a primary tooth with intrusive luxation-type trauma: follow-up of a case - Serrano Cabana , Rina Alexandra (2024)
Trauma in the primary dentition often requires different management than in the permanent dentition. We present the case of an 18-month-old female patient, in apparent good general condition, with no medical history, who came to the pediatric dentistry service of the Teaching Dental Center of the Universidad Peruana Cayetano Heredia because "a tooth had become incrusted when it fell out". After the extraoral examination, edema was observed in the lower lip and intraorally there was an apical displacement of tooth 61. Radiographically, it is observed that tooth 61 is rotated with apical displacement. Diagnosis: Intrusive dislocation of tooth 61 and contusion of the lower lip. Treatment: Washing with physiological saline solution, soft diet, and use of a soft bristle toothbrush; she was kept under observation. Controls: Follow-up was carried out for seven months, during which time spontaneous re-eruption of the affected tooth was observed. Therefore, spontaneous re-eruption is a treatment option in intruded primary teeth after trauma.